Climate policy as expectation management? - Daiju Narita (Kiel Institute for the World Economy (IfW), 2011)
It is often emphasized that the primary economic solution to climate change is the introduction of a carbon pricing system (tax or tradable permits) anchored to the social cost of carbon. This standard argument, however, misses the fact that if emission reduction is sought through the use of technologies with network externalities, the level of emission reduction can become expectation-driven rather than uniquely determined by the level of carbon price. Using a simple model, the paper discusses the possibility that the effectiveness of carbon policy is influenced by firms' belief on carbon policy and technology penetration in the future - in extreme cases, expectations prevail over policy. This feature highlights the danger of overemphasis on finding the 'right' carbon price in policy making and the role of climate policy as expectation management.
Keywords: Q54; O33; 330; Climate policy; technology choice; expectations; multiple equilibria; Klimaschutz; Ökosteuer; Emissionsrechte; Erwartungstheorie; Umwelttechnik; Technologiewahl; Gleichgewicht; Theorie